2023
DOI: 10.3390/land12071459
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Urbanization and Ecological Environment: Coordinated Development and Drivers

Abstract: The interplay between urbanization and ecological environmental efficiency has gained increasing significance in the context of sustainable development, as rapid urban growth poses challenges to resource consumption, greenhouse gas emissions, and the overall ecological well-being of urban areas. Understanding and analyzing the coordinated development of urbanization and ecological environmental efficiency, as well as assessing the influence of drivers on this relationship, is crucial for developing effective p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…This serves as a critical foundation for contemplating the synchronized advancement of regional ecology and environment at the micro level. Firstly, this study measures city size by total urban population, and empirical results confirm that China’s "demographic dividend" initially fostered the synergistic development of urbanization and the environment 74 . However, as urban population expansion remains unchecked, this facilitative effect has transformed into a hindrance.…”
Section: Discussionmentioning
confidence: 67%
“…This serves as a critical foundation for contemplating the synchronized advancement of regional ecology and environment at the micro level. Firstly, this study measures city size by total urban population, and empirical results confirm that China’s "demographic dividend" initially fostered the synergistic development of urbanization and the environment 74 . However, as urban population expansion remains unchecked, this facilitative effect has transformed into a hindrance.…”
Section: Discussionmentioning
confidence: 67%
“…We have selected shared bicycles and new energy cars as our indicators since they are novel, and popular, and haven't been covered in any previous research. For the construction of provincial Chinese green consumption index (GCI) systems, the existing literature has mainly focused on three approaches, namely, mixing urban and rural economic indicators [20,21,25,26], constructing urban GCIs using urban economic indicators [27], and using economic indicators to construct rural GCIs [28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of the study show that digital marketing has been the most important economic factor for both developed and undeveloped countries, outweighing all other factors. The results again revealed that COVID-19 has become an integral part of digital marketing and sustainable economic performance [52][53][54][55][56][57][58][59][60][61][62][63][64][65] in both developed and underdeveloped economies. COVID-19 was associated with innovations, public health, education, vaccines, diagnosis, epidemiology, etc.…”
Section: Introductionmentioning
confidence: 99%